2014
DOI: 10.1128/aac.01018-13
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin Dosing Based on Ideal Body Weight versus Actual Body Weight: Comparison of Clinical Outcomes

Abstract: dDaptomycin use at our institution changed to ideal body weight dosing based on a published analysis of pharmacokinetic-pharmacodynamic efficacy target attainment, bacterial ecology, and a desire to reduce drug toxicity. The current study compared outcomes between actual body weight and ideal body weight dosing of daptomycin before and after this intervention. In the evaluable group, 69 patients received doses based on actual body weight and 48 patients received doses based on ideal body weight. Patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…Monte Carlo simulations of 6 mg/kg dosing based on ABW 0.4 produced AUC values closest to that of nonobese patients and those seen in bacteremia and endocarditis clinical trials . In a retrospective analysis of patients with enterococcal and staphylococcal infections, no difference was reported in outcomes with dosing based on IBW or TBW, despite adjustment for age, sex, BMI, infection type, and organism type . A more recent observational study showed that dosing by ABW provides similar clinical, microbiological, and safety outcomes compared with TBW in obese patients…”
Section: Review Of Specific Antimicrobial Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monte Carlo simulations of 6 mg/kg dosing based on ABW 0.4 produced AUC values closest to that of nonobese patients and those seen in bacteremia and endocarditis clinical trials . In a retrospective analysis of patients with enterococcal and staphylococcal infections, no difference was reported in outcomes with dosing based on IBW or TBW, despite adjustment for age, sex, BMI, infection type, and organism type . A more recent observational study showed that dosing by ABW provides similar clinical, microbiological, and safety outcomes compared with TBW in obese patients…”
Section: Review Of Specific Antimicrobial Agentsmentioning
confidence: 99%
“…73 In a retrospective analysis of patients with enterococcal and staphylococcal infections, no difference was reported in outcomes with dosing based on IBW or TBW, despite adjustment for age, sex, BMI, infection type, and organism type. 74 A more recent observational study showed that dosing by ABW provides similar clinical, microbiological, and safety outcomes compared with TBW in obese patients. 75 Clinicians should be cognizant of daptomycin's dose-dependent musculoskeletal toxicity.…”
Section: Daptomycinmentioning
confidence: 99%
“…The PK-PD characteristics of daptomycin suggest that a 500 mg or 750 mg fixed dose approach is plausible [33][34][35]. 6 mg/kg [36]. If 10 mg/kg were applied based on IBW then doses of approximately 455-776 mg would be computed that matches the aforementioned fixed-dose expectations [33][34][35].…”
Section: Obesity and Initial Dose Selection Approachesmentioning
confidence: 98%
“…53 Am J Health-Syst Pharm-Vol 72 Aug 15, 2015 In July 2010, the University of Wisconsin Hospital and Clinics in Madison converted to daptomycin dosing using ideal body weight (IBW) based on analysis of pharmacokinetic-pharmacodynamic efficacy target attainment, bacterial ecology, and a desire to reduce drug toxicity. In order to describe their experience and compare clinical outcomes between ABW and IBW dosing of daptomycin, Ng et al 11 conducted a retrospective cohort study of patients treated with daptomycin between July 2009 and July 2011, using a preintervention and postintervention analysis. Adult patients with a positive culture who were treated with daptomycin for at least 72 hours were eligible for inclusion.…”
Section: Mortensen Et Al Association Of Azithromycin With Mortalitymentioning
confidence: 99%
“…This study also provides important data regarding the need to carefully select patients who will likely benefit from therapy. 11 Daptomycin is a cyclic lipopeptide antibiotic approved by FDA for the treatment of skin and soft structure infections and S. aureus bacteremia, including right-sided endocarditis. According to the package labeling, daptomycin should be dosed based on actual body weight (ABW); no dosage adjustment is warranted for overweight or obese patients.…”
Section: Mortensen Et Al Association Of Azithromycin With Mortalitymentioning
confidence: 99%